1986
DOI: 10.1079/bjn19860138
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of high intakes of tryptophan, nicotinamide and nicotinic acid in the rat

Abstract: 1. The metabolic fate of high dietary intakes of nicotinamide, nicotinic acid and tryptophan, and of acute doses of nicotinamide and nicotinic acid, has been studied in the rat. A new high-pressure liquid chromatography method for measurement of the principal urinary metabolites of niacin is described.2. Administration to rats of a single oral dose of nicotinamide or nicotinic acid (up to 100 mg/kg body-weight), or maintenance for 3 weeks on diets providing 150 mg nicotinamide or nicotinic acid/kg diet, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
(18 reference statements)
2
35
0
Order By: Relevance
“…In energy rich conditions, NAD + is reduced to nicotine-amide adenine di nucleotide (NADH) and the proportion of NAD + to NADH is reduced during glycolysis, cyclic acid cycling, lipid β-oxidation and protein catabolism [11] . Two main sources of NAD + are the salvage pathway of nicotinamide catalyzed by the enzyme, nicotinamide phosphoribosyltransferase, and de novo synthesis from tryptophan metabolism [12] . Recent experimental studies showed that sirtuins can be found and activated in kidney, liver, spleen, lung, heart, muscle, brain, testis, ovary, thymus, pancreas, white and brown adipose tissue [13] .…”
Section: Cellsmentioning
confidence: 99%
“…In energy rich conditions, NAD + is reduced to nicotine-amide adenine di nucleotide (NADH) and the proportion of NAD + to NADH is reduced during glycolysis, cyclic acid cycling, lipid β-oxidation and protein catabolism [11] . Two main sources of NAD + are the salvage pathway of nicotinamide catalyzed by the enzyme, nicotinamide phosphoribosyltransferase, and de novo synthesis from tryptophan metabolism [12] . Recent experimental studies showed that sirtuins can be found and activated in kidney, liver, spleen, lung, heart, muscle, brain, testis, ovary, thymus, pancreas, white and brown adipose tissue [13] .…”
Section: Cellsmentioning
confidence: 99%
“…In the latter pharmacologic situation, as opposed to nutritional circumstances, different biotransformations for NAmide and NA may explain why they do not have the same pharmacologic action (9). Similarly, in our study (Table 1) NAmide apparently could not be biotransformed into NA in the presence of CLX if CLX inhibited NAmide deamidase activity (9,15).…”
mentioning
confidence: 67%
“…Harmeyer, unpublished results) it was shown that nicotinamide administered into the rumen was almost instantly hydrolysed to nicotinic acid and ammonia, probably due to the presence of microbial deamidases (Warner, 1964) which have also been found in the rat intestines (McCreanor & Bender, 1986). There is also evidence that most tissues can utilize both nicotinic acid and nicotinamide for synthesis of NAD and NADP ).…”
Section: N I a C I N E N T E R I N G T H E R U M E N F R O M T H E D mentioning
confidence: 97%
“…A method for quantification of niacin metabolites from urine using cation-exchange chromatography is, however, available (McCreanor & Bender, 1986). Pertinent methods for determination of the oxidized and reduced forms of the coenzymes in blood and other tissues have been reviewed (Chytil & McCormick, 1986).…”
Section: Assay O F N I a C I N Nad(p) A N D I T S M E T A B O L I Tmentioning
confidence: 99%